The Influence Of Role Prescriptions On The Performance Appraisal Process - Schneier, Craig Eric; Beatty, Richard W. (Academy of Management Journal, 1978)
The article discusses a study which examined the influence of role prescriptions on the performance appraisal process. The advantages of using multiple raters in the performance appraisal process are discussed, and the influence of role prescriptions on ratings is examined. Several charts that list mean ranks for job dimensions as well as mean performance ratings across raters and time periods are presented. The article also discusses the implications of the findings of the research for the practical or operational aspects of appraisal.